2016
DOI: 10.1503/cmaj.151003
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture and splinting versus splinting alone to treat carpal tunnel syndrome: a randomized controlled trial

Abstract: Background:The effectiveness of acupuncture for managing carpal tunnel syndrome is uncertain, particularly in patients already receiving conventional treatments (e.g., splinting). We aimed to assess the effects of electroacupuncture combined with splinting. Methods:We conducted a randomized parallel-group assessor-blinded 2-arm trial on patients with clinically diagnosed primary carpal tunnel syndrome. The treatment group was offered 13 sessions of electroacupuncture over 17 weeks. The treatment and control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
97
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(107 citation statements)
references
References 48 publications
2
97
0
3
Order By: Relevance
“…After screening the full text of the 32 remaining records, we excluded 16 records (see Characteristics of excluded studies), and identified two ongoing studies (see Characteristics of ongoing studies), and two studies awaiting classification (see Characteristics of studies awaiting classification). We included 13 publications from 12 studies (Aigner 1999; Feng 2011; Hadianfard 2015; Jin 2011; Kumnerddee 2010; Li 2011; Ramin 2013; Weinstein 2003; Yang 2009; Yao 2012; Zhang 2011; Chung 2016). Aflowdiagram summarising the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After screening the full text of the 32 remaining records, we excluded 16 records (see Characteristics of excluded studies), and identified two ongoing studies (see Characteristics of ongoing studies), and two studies awaiting classification (see Characteristics of studies awaiting classification). We included 13 publications from 12 studies (Aigner 1999; Feng 2011; Hadianfard 2015; Jin 2011; Kumnerddee 2010; Li 2011; Ramin 2013; Weinstein 2003; Yang 2009; Yao 2012; Zhang 2011; Chung 2016). Aflowdiagram summarising the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, five studies were carried out in mainland China (Feng 2011; Jin 2011; Li 2011; Ramin 2013; Zhang 2011), two in the USA (Weinstein 2003; Yao 2012), one in Germany (Aigner 1999),one in Hong Kong SAR(Chung 2016), one in Iran (Hadianfard 2015), one in Taiwan (Yang 2009), and one in Thailand (Kumnerddee 2010). One study included three comparison groups (Jin 2011), and the remainder compared two comparison groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations